Does the Market Listen to Whispers - BHATTACHARYA, Nilabhra (Institutional Knowledge at Singapore Management University, 2006)
In this study, we investigate the characteristics and information content of whisper forecasts of earnings. Based on data on earnings whispers obtained from public sources and from one private website (‘getwhispers.com’), we examine whether whisper forecasts are more optimistic, on average, than consensus analyst forecasts, and how the market perceives whisper forecasts as compared to consensus analyst forecasts. Our results indicate that whisper forecasts are more optimistic, on average, than consensus analyst forecasts. Further, we find that consensus forecasts are as accurate as whisper forecasts. Our market perception tests reveal that in both the short-run and the long-run, whispers are not incrementally informative to consensus analyst forecasts. Further, we find no evidence that analysts use the information contained in whispers to revise their forecasts. On the contrary, we find that analysts' consensus forecasts often have incremental information content over whisper numbers. However, our inferences are not applicable to recent whisper data since our sample period ends in March 2001. Proprietary ways of analyzing market and street expectations have the potential to add value in picking stocks and assessing market direction. Our findings do not apply to data disseminated via existing, commercial whisper websites that are not part of the sample which may have the potential to add value through proprietary data or analyses using proprietary algorithms.